ROLE OF REFLECTION IN THE PROCESS OF DEVELOPMENT OF SELF-CONSCIOUSNESS IN YOUNGERIC AGE - Kaminska, Olga (PSYCHOLOGICAL JOURNAL, 2017)
The article is devoted to the analysis of the role of reflection in the process of developing the self-consciousness of a person of youth. The views of domestic and foreign scientists on the phenomenon of reflection are analyzed, and its influence on the formation of personality is established. Approaches to the analysis of self-consciousness, its structure and mechanisms are determined. It is established that an important element of self-consciousness is the self-relationship of the individual, which reflects the modality of the perception of the young men themselves and is based on the dominant characteristics of the «I-concept». When conducting an empirical study, the following methods were used: the method for determining the level of development of reflexivity Karpova, test of twenty assertions of the self-relationship of M. Kuhn and T. Mak Partland, test-questionnaire of self-relations V.V. Stolin. During the research, differences in the ratio of perceptual and reflexive characteristics were revealed. Thus, in girls the reflexive characteristics are much more prevalent. This indicates that the girls better understand their personal characteristics and the characteristics of their own «I». Young people are guided by the assessment of others, which is often ambiguous and inconsistent, which prevents the formation of a clear and deep «I-image». From this follows the tendency to overstate the young men of their self-esteem, as he ceases to notice negative information about himself and focuses only on positive assessments of others, which helps to avoid inconsistency or reduce self-esteem. Empirically, the level of development of reflexion in young men has been studied and its relation to the specifics of the self-relationship as a component of self-consciousness has been established. It is proved that the high level of development of reflexion in adolescence correlates with the adequacy of self-relationship, self-esteem, autosympathy, self-acceptance and, to the greatest extent, self-understanding.